2021
DOI: 10.1016/j.ijid.2021.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab and Systemic Corticosteroids in the Management of Patients with COVID-19: A Systematic Review and Meta-Analysis

Abstract: Background : To date, there is no effective treatment for the new coronavirus (COVID-19). We aimed to systematically review the literature on the association between the combination of tocilizumab (TCZ) and systemic corticosteroid therapy (SCT) on outcomes of COVID-19 patients. Methods : We searched MEDLINE, Cochrane Central, and preprints, for studies in which health outcomes were compared between adults with severe COVID-19 who received TCZ and SCT and those who recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…The patients suffer CSS elevated levels of cytokines thus raising interleukin-6 (IL-6), interleukin-10 (IL-10) and interferon-gamma (IFN-γ). The scientific reports indicate that the SARS-CoV-2 infection is associated with a significant increase in IL-6 [ 51 , 52 ]. Tocilizumab is a monoclonal antibody that inhibits IL-6, and the FDA has already granted emergency use authorization for the management of COVID-19 related CSS and organ failure.…”
Section: Main Textmentioning
confidence: 99%
“…The patients suffer CSS elevated levels of cytokines thus raising interleukin-6 (IL-6), interleukin-10 (IL-10) and interferon-gamma (IFN-γ). The scientific reports indicate that the SARS-CoV-2 infection is associated with a significant increase in IL-6 [ 51 , 52 ]. Tocilizumab is a monoclonal antibody that inhibits IL-6, and the FDA has already granted emergency use authorization for the management of COVID-19 related CSS and organ failure.…”
Section: Main Textmentioning
confidence: 99%
“…23 It was reported that in subjects with severe COVID-19, the use of both TCZ and systemic corticosteroid therapy compared to no TCZ treatment reduced the risk of mortality. 24 For severe COVID-19 patients, the addition of TCZ to the standard of care may reduce mortality and the need for mechanical ventilation. 25 A meta-analysis that included 25 peerreviewed publications determined that TCZ treatment is related to a decreased risk of mortality and the need for mechanical ventilation, as well as a better prognosis in COVID-19 patients, particularly those who are critically ill. 26 In the unmatched population, patients who received TCZ had greater NIMV, HFNO, mechanical ventilation requirements, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized controlled trials (RCTs) and cohort studies have been conducted in search of effective therapies for COVID-19 with conflicting results [1] , [6] , [7] , [8] , [9] , [10] , [11] , [12] . Systemic corticosteroids were the first of these treatments which showed mortality benefits in patients who received oxygen and ventilatory support in the RECOVERY trial [10] .…”
Section: Introductionmentioning
confidence: 99%